Small bowel obstruction after transoral robotic surgery. Issue 1 (9th November 2017) - McClellan, Joseph; Achim, Virginie; Clayburgh, Daniel
Abstract: Background: Head and neck surgery is not often considered a risk factor for intestinal ileus and small bowel obstruction. However, many of these patients may have had prior abdominal surgery, a known risk factor for small bowel obstruction, and may be at risk for bowel obstruction after a surgical procedure of the head and neck. Methods: We present a case describing a patient who, after undergoing transoral robotic surgery, experienced delayed postoperative ileus and eventual small bowel obstruction requiring exploratory laparotomy and bowel resection. Results: Although the patient required total parenteral nutrition for several days, he eventually was able to resume tube feeds, and after several months was able to tolerate an oral diet. Conclusion: Although uncommon complications of head and neck surgery, intestinal ileus and small bowel obstruction can develop as the result of stress/inflammation, postoperative narcotic pain medication, and prior abdominal surgery.